2014
DOI: 10.3109/14767058.2014.954243
|View full text |Cite|
|
Sign up to set email alerts
|

Sterile intra-amniotic inflammation in asymptomatic patients with a sonographic short cervix: prevalence and clinical significance

Abstract: Objective To determine the frequency and clinical significance of sterile- and microbial-associated intra-amniotic inflammation in asymptomatic patients with a sonographic short cervix. Methods Amniotic fluid (AF) samples obtained by transabdominal amniocentesis from 231 asymptomatic women with a sonographic short cervix [cervical length (CL) ≤25 mm] were analyzed using cultivation techniques (for aerobic and anaerobic as well as genital mycoplasmas) and broad-range polymerase chain reaction (PCR) coupled wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
130
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(142 citation statements)
references
References 294 publications
(249 reference statements)
4
130
0
8
Order By: Relevance
“…It is noteworthy that the frequency of acute chorioamnionitis in patients who delivered between 21 to 24 weeks of gestation was 94.4% (17/18) 2 . This is consistent with extensive studies subsequently reported by our group 17, 18 and others 19, 20 , and emphasizes the importance of acute inflammation in early preterm deliveries and midtrimester spontaneous abortions.…”
Section: Prevalence Of Acute Histologic Chorioamnionitissupporting
confidence: 93%
“…It is noteworthy that the frequency of acute chorioamnionitis in patients who delivered between 21 to 24 weeks of gestation was 94.4% (17/18) 2 . This is consistent with extensive studies subsequently reported by our group 17, 18 and others 19, 20 , and emphasizes the importance of acute inflammation in early preterm deliveries and midtrimester spontaneous abortions.…”
Section: Prevalence Of Acute Histologic Chorioamnionitissupporting
confidence: 93%
“…81 Other alarmins including IL-1a, heat shock protein 70, and calcium-binding protein B have been reported to have similar effects in inducing labor. 22 Prevalence and clinical significance of sterile inflammation has been reported recently by Romero et al 23,82,83 in multiple pregnancy-associated conditions. We postulate that inflammatory responses seen at term labor likely result from fetal cell senescence, signaling readiness for parturition.…”
Section: Sterile Inflammation: a Trigger For Labormentioning
confidence: 89%
“…Most work in clinical chorioamnionitis has been based on a case definition that relies heavily on clinical signs. The shortcomings of such an approach have become clear, now that sterile inflammation has emerged as an important entity for patients at term (137) as well as for those in preterm labor (83, 86), those with preterm prelabor rupture of the membranes (84), or those with an asymptomatic sonographic short cervix (85). Non-microbial-associated inflammation appears to account for a sizable segment of patients with clinical chorioamnionitis at term (69, 80).…”
Section: Discussionmentioning
confidence: 99%